DAKWAH MELALUI FILM - Efendi P. (AL TAJDID, 2009)
Dakwah by film is better solution to change human feeling. Film as one of media have attractiveness to audience, not only when they watching, but it can be long time. Because what they seen is the same of reality, so they can influence. In other that, film as one of media to give religious information to society